2010
DOI: 10.1177/1479164110383723
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Coagulation and fibrinolysis in diabetes

Abstract: Atherothrombotic complications are the main cause of mortality in subjects with diabetes. Premature atherosclerosis, increased platelet reactivity and activation of coagulation factors with associated hypofibrinolysis all contribute to increased cardiovascular risk in this population. Blood clot formation represents the last step in the atherothrombotic process, and the structure of the fibrin network has a role in determining predisposition to cardiovascular disease. In this review, we discuss alterations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
188
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(209 citation statements)
references
References 138 publications
8
188
0
6
Order By: Relevance
“…This study has demonstrated that not only the plasma levels of TF but also TFPI were higher in type 2 diabetes mellitus (T2DM) patients; however, only uncontrolled with microalbuminuria. The TF expression by endothelial cells is found in trace amounts in the resting state; however, that synthesis is upregulated in the presence of inflammation, which is commonly associated with diabetes type 2 (Alzahrani and Ajjan, 2010;Breitenstein et al, 2010). The TF level does not always correlate with the activity of TF, it is probably related to the simultaneous synthesis of the TFPI by the endothelial cells (Steffel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study has demonstrated that not only the plasma levels of TF but also TFPI were higher in type 2 diabetes mellitus (T2DM) patients; however, only uncontrolled with microalbuminuria. The TF expression by endothelial cells is found in trace amounts in the resting state; however, that synthesis is upregulated in the presence of inflammation, which is commonly associated with diabetes type 2 (Alzahrani and Ajjan, 2010;Breitenstein et al, 2010). The TF level does not always correlate with the activity of TF, it is probably related to the simultaneous synthesis of the TFPI by the endothelial cells (Steffel et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms for altered clot structure in diabetes are multifactorial: firstly, high plasma glucose can lead to increased glycations of fibrinogen and fibrin, which is associated with a more massive clot structure, which, in turn, favors resistance to lysis; secondly, elevated plasminogen activator inhibitor (PAI)-1 level reduces the fibrinolytic potential; thirdly, the non-enzymatic glycations of plasminogen and decreased activities of protein C act as the inhibitors of PAI-1 (Alzahrani and Ajjan, 2010). This study has demonstrated that not only the plasma levels of TF but also TFPI were higher in type 2 diabetes mellitus (T2DM) patients; however, only uncontrolled with microalbuminuria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well recognized that chronic hyperglycemia promotes the development of atherothrombosis in diabetes by a concatenation of events that leads to increased atherosclerotic plaque formation and rupture, enhanced platelet activation, and increased thrombus formation [20,21]. Mechanisms for increased thrombosis risk include increased platelet activation as well as quantitative and qualitative changes in coagulation proteins such as plasminogen activator inhibitor-1 (PAI-1), fibrinogen, and plasminogen generating a denser fibrin clots that are resistant to fibrinolysis [22][23][24][25][26].…”
Section: Effect Of Hypoglycemia On the Coagulation Systemmentioning
confidence: 99%